Transient receptor potential channels’ genes forecast cervical cancer outcomes and illuminate its impact on tumor cells - Jiang, Shan; Lin, Xuefen; Wu, Qiaoling; Zheng, Jianfeng; Cui, Zhaolei; Cai, Xintong; Li, Yanhong; Zheng, Chaoqiang; Sun, Yang (Frontiers in Genetics, 2024)
In recent years, there has been a strong association between transient receptor potential (TRP) channels and the development of various malignancies, drug resistance, and resistance to radiotherapy. Consequently, we have investigated the relationship between transient receptor potential channels and cervical cancer from multiple angles. Patients' mRNA expression profiles and gene variants were obtained from the TCGA database. Key genes in transient receptor potential channel prognosis-related genes (TRGs) were screened using the least absolute shrinkage and selection operator (LASSO) regression method, and a risk signature was constructed based on the expression of key genes. Various analyses were performed to evaluate the prognostic significance, biological functions, immune infiltration, and response to immunotherapy based on the risk signature. Our research reveals substantial differences between high and low-risk groups in prognosis, tumor microenvironment, tumor mutational load, immune infiltration, and response to immunotherapy. Patients in the high-risk group exhibited poorer prognosis, lower tumor microenvironment scores and reduced response to immunotherapy while showing increased sensitivity to specific targeted drugs. In vitro experiments further illustrated that inhibiting transient receptor potential channels effectively decreased the proliferation, invasion, and migration of cervical cancer cells. In conclusion, this study highlights the significant potential of transient receptor potential channels in cervical cancer, emphasizing their crucial role in prognostic prediction and personalized treatment strategies. The research shows the significance of transient receptor potential channels in cervical cancer, highlighting their crucial role in prognostic prediction and personalized therapeutic strategies. The combination of TRP inhibitors with immunotherapy and targeted drugs offers promise for individuals affected by cervical cancer.